PREVALENCE AND RISK FACTORS OF HOOKWORMS INFECTION ON DOGS IN SUKABUMI REGENCY, WEST JAVA PROVINCE, INDONESIA - Yusuf Ridwan; Ardilasunu Wicaksono; Siti Vanessa Fransiska; Princesse Theresa (Universitas Syiah Kuala, 2020)
Hookworms infection remains as an important parasitic infections affecting animal and human health worldwide. However, information on the prevalence and the risk factors of hookworm infection on dogs in Indonesia is very limited. A cross sectional study to estimate the prevalence and to identify risk factors of hookworms infection on dogs was conducted in rural area with different topography, Sukabumi Regency, Indonesia. A Total of 204 dog stool specimens were examined for hookworm eggs using simple flotation methods. The data of related risk factors namely type of topography area (high and low land), purpose of having dog, dog demography, dog reared management and deworming were collected through dog owners interview’s with completed a questionnaire. Those data were analyzed using the chi-square test (χ2) and logistic regression. The prevalence of hookworm on dogs in Sukabumi was 24.5 % (95% Confidence Interval [CI]=19.1-30.8). This prevalence was associated with topography of the area, the age of dog, and type of dog keeping methods. The prevalence of hookworms was higher in the high land area than low land area (OR=5.935, 95% CI=2.764-12.744 ). Logistic regression identified pupies as a high risk group to hookworms infection (OR= 2.041, 95%CI=1.035-4.055). The dog which kept in the cage/tied had higher risk than free roaming dog (OR=3.66, 95%CI=1.479-9.091).Key words: Dog, hookworms, prevalence, risk factors, Sukabumi.